PROJECT - BASED EDUCATION MANAGEMENT MODEL BASED ON IDDHIPADA PRINCIPLES OF ANGTHONG VOCATIONAL EDUCATION INSTITUTE UNDER THE OFFICE OF THE VOCATIONAL EDUCATION COMMISSION - Mongkolthong, Suwatchai; Chomnisat , Boonchead; Klomkul, Lampong (Journal of Educational Review Faculty of Education in MCU, 2024)
This research article aimed to propose a model of project-based education based on the principle of the Four Iddhipda of vocational educational institutions in Ang Thong Province, under the Office of the Vocational Education Commission. This research was a mixed-method research with 3 research steps as following: Step 1: quantitative research using a questionnaire with a sample of 165 teachers. Step 2: qualitative research by interviewing 6 key informants and group discussions with 9 experts using purposive selection. Step 3: model evaluation by using an evaluation form with a sample of 165 teachers of vocational educational institutions in Ang Thong Province, under the Office of the Vocational Education Commission. Data were analyzed using statistics including frequency, percentage, mean, and standard deviation. The research results revealed that the model of project-based education based on the principle of the Four Iddhipda of vocational educational institutions in Ang Thong Province, under the Office of the Vocational Education Commission, had 4 components: 1) principle, 2) objective, 3) integration of project-based education based on the principle of the Four Iddhipda, and 4) 7 aspects of application, namely planning and goal setting, project creation, the introduction of project management systems, supporting and personnel development, cooperation building, measurement and evaluation, promotion and dissemination, and the results of format evaluations were all at the highest level overall. When considering each aspect, it was found that the evaluation results were at the highest level in all 4 aspects: usefulness, feasibility, appropriateness, and correctness, respectively. It was summarized as the research knowledge, namely 3PIC.